2018
DOI: 10.5603/gp.a2018.0022
|View full text |Cite
|
Sign up to set email alerts
|

HSD3B2, HSD17B1, HSD17B2, ESR1, ESR2 and AR expression in infertile women with endometriosis

Abstract: Observed significant increase in HSD3B2 and ESR1 transcripts in follicular eutopic endometrium from infer-tile women with endometriosis may be related to abnormal biological effect of E2 in endometrium, further affecting the development of human embryos.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 30 publications
(55 reference statements)
0
16
0
1
Order By: Relevance
“…These GWAS results are not surprising since the symptoms of endometriosis are modulated by ovarian sex steroids; early age at menarche is a risk factor for development of endometriosis, suggesting increased exposure to estrogen may incur increased risk of disease (26). Endometriosis lesions aberrantly express a number of steroidogenic enzymes including aromatase and 17β-hydroxysteriod dehydrogenase (17β-HSD), this results in increased synthesis and decreased metabolism of estrogen (27)(28)(29) such that local levels remain high. Estrogen signaling modulates a large number of down-stream disease processes within endometriosis lesions, which are reviewed in Yilmaz and Bulun (30), Liang et al (31), and Rizner (32).…”
Section: Etiology and Natural Historymentioning
confidence: 97%
“…These GWAS results are not surprising since the symptoms of endometriosis are modulated by ovarian sex steroids; early age at menarche is a risk factor for development of endometriosis, suggesting increased exposure to estrogen may incur increased risk of disease (26). Endometriosis lesions aberrantly express a number of steroidogenic enzymes including aromatase and 17β-hydroxysteriod dehydrogenase (17β-HSD), this results in increased synthesis and decreased metabolism of estrogen (27)(28)(29) such that local levels remain high. Estrogen signaling modulates a large number of down-stream disease processes within endometriosis lesions, which are reviewed in Yilmaz and Bulun (30), Liang et al (31), and Rizner (32).…”
Section: Etiology and Natural Historymentioning
confidence: 97%
“…The Δ 5 to Δ 4 isomerization of androstenes (DHEA, androstenediol -A5- and 17αA5) and pregnenes (P5, 17OHP5) is catalyzed by 3βHSD1, which is the peripheral counterpart of ovarian 3βHSD2. Also 3βHSD2, whose expression was initially considered to be restricted to endocrine tissues, is detected peripherally in recent reports (Stoffel-Wagner, 2001 ; Tsai et al, 2001 ; Attar et al, 2009 ; Huhtinen et al, 2014 ; Osinski et al, 2018 ). Due to the high concentration of DHEA (both in blood and tissues), its conversion to A4 by 3βHSDs is relevant to the formation of downstream androgens and of estrogens.…”
Section: From Ovarian Estrogen Synthesis To Intracrinologymentioning
confidence: 98%
“…Since E2′s effects are primarily enacted through ESR1 and ESR2, their expression levels are important in the assessment of E2 action in endometriosis. ESR1 levels are reportedly increased in the secretory phase endometrium of women with endometriosis compared to controls [172,173], which may lead to increased estrogenic activity and proliferation, compromising normal uterine function. ESR2 expression is unchanged in eutopic endometrium from women with endometriosis [173] although one study reported increased ESR2/ESR1 ratio in endometriosis-affected endometrium [174].…”
Section: Dysregulation Of Progesterone and Estrogen Signaling In Ementioning
confidence: 99%
“…ESR1 levels are reportedly increased in the secretory phase endometrium of women with endometriosis compared to controls [172,173], which may lead to increased estrogenic activity and proliferation, compromising normal uterine function. ESR2 expression is unchanged in eutopic endometrium from women with endometriosis [173] although one study reported increased ESR2/ESR1 ratio in endometriosis-affected endometrium [174]. The role of ESR2 in normal uterine physiology is not clear since ESR2 knockout mice have been reported to have no overt uterine defect [76,77]; however, one study implicated ESR2 in control of proliferation through epidermal growth factor (EGF) signaling [78].…”
Section: Dysregulation Of Progesterone and Estrogen Signaling In Ementioning
confidence: 99%